THE INFLUENCE OF EU LAW ON POLISH CRIMINAL LAW FOR THE PREVENTION OF ILLEGAL IMMIGRATION - Perkowska, Magdalena (Zeszyty Prawnicze, 2021)
The main aim of this paper is to examine whether or not the legal amendments to Polish criminal law for the prevention of illegal immigration were necessary and if so, whether they are proportional to the perceived threat posed by such migration. The paper discusses the implementation of the relevant EU legislation, viz. Council Framework Decision 2002/946/JHA of 28 November 2002 on the strengthening of the penal framework to prevent the facilitation of unauthorised entry, transit and residence; Council Directive 2002/90/EC defining the facilitation of unauthorised entry, transit and residence; Directive 2009/52/WE/EC of the European Parliament and of the Council providing for minimum standards on sanctions and measures against employers of illegally resident third-country nationals; and the Council of Europe Convention on the Prevention of Terrorism; and the direct eﬀects of this legislation on Polish criminal law as presented in the Polish Criminal Code (Arts. 264a and 259a k.k.), the aggravation of the penalties in Art. 264 § 3 k.k.; and the institution of Ustawa o skutkach nielegalnego zatrudnienia cudzoziemców nielegalnie przebywających na terytorium Polski (the Act on Liability for the Employment of Illegal Immigrants on Polish Territory). In addition, the article considers the eﬀectiveness of the new criminal provisions, particularly on the basis of the number of convictions.